Blockchain Adoption Barriers and Stakeholder Readiness for Halal Food Supply Chain Integration - Umi Cholifah; Deasy Wulandari; Aulia Arifatu Diniyya (Journal of Digital Marketing and Halal Industry, 2026)
Blockchain technology offers an innovative solution to transparency challenges in halal food supply chains. However, prior literature heavily overlooks the entry-stage dynamics of small-scale ecosystems, often misclassifying cost and regulation as insignificant factors. This study addresses this gap by investigating the multi-dimensional readiness and adoption barriers within the Halal, Safe, and Healthy Culinary Zone (Zona KHAS) in Indonesia. Employing a qualitative exploratory design, the methodology uniquely triangulates strategic macro perspectives (expert FGDs and policy documents) with operational micro realities (stakeholder surveys and field observations). These complementary data streams were synthesized using NVivo 15 thematic analysis to bridge empirical viewpoints. The findings yield a crucial theoretical insight: cost (estimated USD 15,000–25,000/year) and regulatory complexities act as severe, structural 'barriers to entry' for MSMEs, directly contradicting established supply chain models. To overcome these challenges, this study develops an original, phased implementation framework that initiates blockchain integration upstream (producers) within a controlled pilot ecosystem. This framework offers concrete managerial and policy implications by providing a realistic, risk-mitigating pathway for regulators and Zona KHAS managers to systematically scale digital halal assurance.